Electronic structure, optical and vibrational properties of Ti2FeNiSb2 and Ti2Ni2InSb double half heusler alloys. (1st March 2021) - Uğur, G.; Kushwaha, A.K.; Güler, M.; Charifi, Z.; Uğur, Ş.; Güler, E.; Baaziz, H.
Abstract: We report the structural, elastic, electronic, optical and vibrational properties of double half Heusler (DHH) compounds Ti2 FeNiSb2 and Ti2 Ni2 InSb within density functional theory (DFT) for the first time. The calculated elastic constants express that both compounds are mechanically stable and show ductile mechanical character. Computed band structures of these compounds indicate typical semiconductor behaviour with the band gap energies of 0.63 eV for Ti2 FeNiSb2 and 0.42 eV for Ti2 Ni2 InSb. We have also searched the optical properties such as the dielectric function, optical conductivity, refractive index, absorption index and reflectance for both compounds. Besides, we have computed vibrational properties i.e. zone-centre Raman and infrared phonon modes along with the phonon dispersion relations and phonon density of states of surveyed compounds.